DIALOGUE AS A MEANS OF CREATIVE PERSONALITY DEVELOPMENT IN THE PROCESS OF STUDYING BIOCHEMISTRY - N.O. Chuvasova (Academy of Cognitive and Natural Sciences, 2010)
The article considers some peculiarities of the dialogue as a way of the development of the creative personality in the course of biochemistry studying.